THE DIFFERENCES BETWEEN ENGLISH AND INDONESIAN LANGUAGE - Sholihah, Umi (MAGISTRA, 2014)
Languages are different, eventhough they have similarities too. They have own rules of usage. English as the first foreign language which is taught in Indonesia has many differences with Indonesian language. Some of the differences are found in syntax, phonemes, pronunciation, meaning, grammar, and tenses. The differences often make students are difficult to understand in learning English. As English teachers, we should know those differences well in order to give enough understanding in teaching English for our students. This article will discuss about some differences between English and Indonesian language, completed with their examples. Hope after having deep understanding of those differences, we are as the English teacher, will find, modify, and create new methods of teaching so that the students will be easier to learn English. Keywords: differences, language, English, Indonesian